PENYELESAIAN SENGKETA TUMPANG TINDIH HAK ATAS TANAH YANG DITERBITKAN DARI PENDAFTARAN TANAH SISTEMATIK LENGKAP - Febriyanto, Harry Isha; Hutomo, Putra; Ridwan, Refki (Case Law : Journal of Law, 2025)
The issuance of certificates of overlapping land rights gives rise to land disputes involving the Land Office as the authorized official and also the community who own the land rights. This research aims to examine and analyze dispute resolution over overlapping land title certificates issued based on PTSL using dispute resolution theory (Dean G. Pruitt and Jeffrey Z. Rubin). This research uses a type of normative juridical research with a statutory approach, conceptual approach and case approach. The technique for collecting legal materials is carried out by studying documentation of sources of legal materials regarding the implementation of Complete Systematic Land Registration. The analysis technique for legal materials is carried out using grammatical legal interpretation and analogous legal construction methods. The results of the research can be concluded that resolving disputes over overlapping land title certificates issued based on PTSL can generally be carried out through administrative procedures that refer to Article 66 in the ATR/BPN Ministerial Regulation Number 11 of 2016 concerning Settlement of Land Disputes and court decisions to provide legal certainty of ownership of disputed land rights.